Work participation in adults with rare genetic diseases - a scoping review - Gry Velvin; Brede Dammann; Trond Haagensen; Heidi Johansen; Hilde Strømme; Amy Østertun Geirdal; Trine Bathen (BMC, 2023)
Abstract Background Work participation is a crucial aspect of health outcome and an important part of life for most people with rare genetic diseases. Despite that work participation is a social determinant of health and seems necessary for understanding health behaviours and quality of life, it is an under-researched and under-recognized aspect in many rare diseases. The objectives of this study was to map and describe existing research on work participation, identify research gaps, and point to research agendas in a selection of rare genetic diseases. Methods A scoping review was performed by searching relevant literature in bibliographic databases and other sources. Studies addressing work participation in people with rare genetic diseases published in peer reviewed journals were assessed using EndNote and Rayyan. Data were mapped and extracted based on the research questions concerning the characteristics of the research. Results Of 19,867 search results, 571 articles were read in full text, and 141 satisfied the eligibility criteria covering 33 different rare genetic diseases; 7 were reviews and 134 primary research articles. In 21% of the articles the primary aim was to investigate work participation. The extent of studies varied between the different diseases. Two diseases had more than 20 articles, but most had only one or two articles. Cross-sectional quantitative studies were predominant, with few utilizing prospective or qualitative design. Nearly all articles (96%) reported information about work participation rate, and 45% also included information about factors associated with work participation and work disability. Due to differences in methodologies, cultures and respondents, comparison between and within diseases are difficult. Nevertheless, studies indicated that many people with different rare genetic diseases experience challenges related to work, closely associated to the symptoms of the disease. Conclusion While studies indicate high prevalence of work disability in many patients with rare diseases, the research is scarce and fragmented. More research is warranted. Information about the unique challenges of living with different rare diseases is crucial for health and welfare systems to better facilitate work participation. In addition, the changing nature of work in the digital age, may also open up new possibilities for people with rare genetic diseases and should be explored.